Capacitating Extension Workers and Trainers for Soil Health: ICRISAT’s Contribution to the Soil Values Project in Mali - Traore, Bouba; Sinare, Boubacar; Kassé, Hama; Maman, Bizo I.; Desta Gizaw; Moyo, Martin (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Under the Soil Values Programme, ICRISAT implemented a set of strategic actions aimed at strengthening soil fertility, soil health, and climate resilience through evidence-based tools and capacity development of extension workers and community trainers. Activities were implemented across three priority watersheds in Mali: Upper Bani (Sikasso), Upper Niger Basin (Ségou), and Middle Bani (San–Tominian). The interventions focused on three complementary pillars:(i) the development of a zonal catalogue of improved crop varieties, forage species, and woody species adapted to local agroecological conditions; (ii) capacity strengthening of public extension agents, NGOs, and community trainers on climate information services and Climate-Smart Agriculture (CSA); and (iii) training of farmer-trainers on Sustainable Land Management practices, particularly Soil and Water Conservation / Soil Defense and Restoration (SWC/SLM).